Baseline quality of life is associated with survival among people with advanced lung cancer. Issue 5 (2nd September 2020) - Trejo, Mario J.; Bell, Melanie L.; Dhillon, Haryana M.; Vardy, Janette L.
Abstract: Introduction: Lung cancer patients presenting with advanced cancer face low survival rates and a high symptom burden. There have been mixed findings for the association between survival and various patient reported outcomes (PROs). Methods: We used prospective data from 111 lung cancer patients with advanced stage III/IV disease to investigate the association of survival with PROs (European Organization for Research and Treatment of Cancer Core-30 and Lung Module). Cox proportional hazard models were used to examine the individual association between several PRO measures and survival. Results: Pain in chest and global quality of life (QoL) were found to have the strongest association with survival with a 20% increased hazard of death per 10% increase in pain in chest and 14% decrease in hazard of death per 10% increase in global QoL. Conclusion: Our results provide more evidence for the value of PRO data to inform clinical and patient decision-making.